P021 Use of non-FDA cleared assays for detection of STIs in children being evaluated for suspected sexual abuse. (14th July 2019) - Hammerschlag, Margaret; Brownell, Amanda; Shapiro, Robert
Abstract : Background: Although NAAT testing is the gold-standard for C. trachomatis (Ct) and GC in adults, limited data exists for children. Although there are now 7 FDA cleared Ct/GC NAATs in the US, assays that are not FDA cleared have been proliferating. Methods: We present 3 instances where non approved assays were used in children being evaluated for suspected sexual abuse. Results: The tests were Vaginitis Plus NuSwab® (LabCorp, North Carolina) which tests for BV, Candida species, Ct, GC, and T. vaginalis (Tv), Diatherix Laboratories NAAT for GC, Ct and Tv (Huntsville, Alabama) and 'Leukorrhea Panel' (MDLabs, NJ), R-T PCR for Tv, GC and Ct. These tests are not FDA-cleared. There are no studies on the performance of these assays in men or women in the peer-reviewed literature including sensitivity, specificity (including cross reactivity with other bacteria) and predictive values for any anatomic site. MDLabs also claimed that their assay did 'reflex' antibiotic suseptibility testing for GC and Ct. A 11 yo girl with a positive NuSwab for Ct subsequently tested negative by TMA. A 2 yo boy tested positive for GC by Diatherix in a rectal specimen, which was discarded after 7 days. The Diatherix manual specifically stated that the test should not be used for rectal specimens. Two siblings tested positive in throat for GC by the 'Leukorrhea Panel' after disclosure of oral penile contact, but father was negative for GC. Specimens were not retained for confirmatory testing. Conclusion: Because of low STI disease prevalence in children (< 3%), low test specificity calculates to an unacceptably low positive predictive value. None of these labs retained the specimens for confirmatory testing, a major departure from CDC recommendations. Use of NAATs that have not been cleared by any regulatory agency without reliable test specificity data can have criminal and juvenile protection implications when used in children. Disclosure: No significant relationships.